SKRINING FITOKIMIA DAN UJI AKTIVITAS EKSTRAK ETANOL RUMPUT LAUT MERAH (GRACILARIA VERRUCOSA) TERHADAP PENYEMBUHAN LUKA SAYAT PADA TIKUS PUTIH JANTAN GALUR WISTAR - Aprinaldi, Bilal (P3M STIKes Bakti Tunas Husada, 2020)
Wound is defined as the disruption of the anatomic and cellular continuity of tissue caused by chemical, thermal ,physical, immunological and microbial, or injury to the tissue. Seaweed contains secondary metabolites such as flavonoids and saponins. Red seaweed contains albumin which can accelerate the process of wound healing. This study aims to determine the concentration of red seaweed ethanol extract which has an effect as a wound wound healing and to determine the length of wound healing from each concentration. A total of 25 rats were divided into 6 groups consisting of positive control given 10% povidone iodine ointment, negative control given vaseline albumin, Group 1 (Concentration 7.5% ethanol extract of red seaweed), group 2 ( Concentration 15 % ethanol extract of red seaweed, group 2 ( Concentration 30% ethanol extract of red seaweed). Phytochemical screening on ethanol extracts of red seaweed showed the presence of secondary metabolites such as flavonoids, saponins, quinones, monoterpenes and sesquiterpenes. Albumin identification shows positive results. Changes in wound area or wound surface were observed by measuring the diameter of the wound from days 1 to 16, and the diameter of the wound was converted into percent using the Morton method. Data analysis using non-parametric tests. The analysis showed a significant difference (p <0.05) between the positive and negative control groups, and there was no difference between positive controls with concentrations of 7.5%, 15%, 30% on the 4 day. The 30% concentration is the group that provides the fastest wound healing effect on the 12 day when compared to the 7.5% and 15% concentration groups . The results of this study indicate that ethanol extract of red seaweed has a healing effect on the wound.